Work Stress Has An Impact On Employee Performance With Work Environment Variables As Moderation - Meutia, Kardinah Indrianna; Narpati, Bintang (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
This comprehensive study delves into the critical nexus between workplace stress and its reverberations on employee performance, all within the context of a dynamic work environment. The research methodology employs the well-regarded Slobin formula coupled with a straightforward random sampling approach. A meticulously crafted questionnaire facilitated the collection of data from a substantial cohort of 85 respondents, providing a robust foundation for analysis. The findings gleaned from this study affirm, in part, the palpable influence of work-related stress on employee performance. Notably, the presence of moderating variables within the work environment plays a pivotal role in ameliorating this impact, ultimately enhancing employee output and efficiency. Through rigorous statistical scrutiny, it was determined that the work stress variable accounted for 15.70% of the variation in employee performance before any mitigating measures were taken. This percentage saw a notable surge, escalating to 54.30%, after factoring in the influence of the work environment variable. Consequently, it can be discerned that a considerable 38.60% enhancement in employee performance is attributable to the amelioration of the work environment. These results substantiate the crucial importance of not only recognizing and addressing workplace stress but also tailoring the work environment to foster a more conducive and productive professional milieu.